EAHIL Council Elections 2015-2018 Outcome of elections (Journal of EAHIL, 2014)
This summary table presents EAHIL countries, number of Council, vacancies for the 2015-2018 term, candidates for election, number of votes received for each candidate, and confirmation of successful candidates. Congratulations and welcome to our new and returning Councillors! In one case there is a tie in the number of votes between two candidates (Sweden). According to our rules of procedure (5.b.), ‘Where two or more candidates receive the same number of votes, the election shall be determined by lot’ so a well-witnessed drawing of lots will take place at the next EAHIL Board meeting in February 2015.The voting was conducted electronically over the period 25 October until 14 November 2014. We are very grateful to Suzanne Bakker, Secretariat Supervisor, who managed the online system used for the vote, and to our Election Committee members, Helena Buzkova, Katri Larmo and Linda Lisgarten, who audited the process, system and outcomes.